Social, affective, and non-motoric bodily cues to the Sense of Agency: A systematic review of the experience of control. (November 2022) - Villa, Riccardo; Ponsi, Giorgia; Scattolin, Marina; Panasiti, Maria Serena; Aglioti, Salvatore Maria
Abstract: While the Sense of Agency (SoA) – the experience of controlling actions – is linked to motoric processes, the effects of non-motoric cues remain uncertain. We performed a systematic review investigating whether SoA is modulated by social, affective, and non-motoric bodily cues like internal bodily signals (IBSs) and Sense of Ownership (SoO). We searched Scopus and Pubmed and checked additional sources (e.g., citation searching). We identified 160 articles investigating social (67), affective (71) and non-motoric bodily cues (28), and calculated the percentage of studies supporting SoA modulation. SoA is influenced by social cues (92.54%), like the presence of interactive agents, and their status. Concerning affective cues (88.73%), reward-related information and affective states modulate SoA, but the effects of outcome valence are inconsistent. Regarding bodily cues (78.57%), SoO informs SoA, but the impact of IBSs is unclear. Overall, we show that diverse non-motoric cues modulate SoA. We submit that the brain evaluates different non-motoric cues in partially distinct circuits, before comparing them in a fronto-parietal network grounding SoA modulation. Highlights: The Sense of Agency (SoA) has been classically linked to motoric processes. The impact of non-motoric cues on SoA remains unclear. We performed a systematic review of studies examining non-motoric cues to SoA. Social, affective, and non-motoric bodily cues each have unique effects on SoA. The brain may adjust SoA via cue-specific and shared fronto-parietal circuits.